2006
DOI: 10.1007/s00421-006-0219-4
|View full text |Cite
|
Sign up to set email alerts
|

Different vascular responses in glabrous and nonglabrous skin with increasing core temperature during exercise

Abstract: To elucidate the characteristics of vasomotor control in glabrous and nonglabrous skin during dynamic exercise, we compared the vascular responses in both areas to increasing core temperature during the cycle exercise for 30 min at different intensities in the range 20-60% of peak oxygen consumption (VO(2peak)) in a total of 13 male and four female subjects in two experimental protocols. Skin blood flow was monitored using laser Doppler flowmetry. In protocol 1, the slope of the relationship between esophageal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 29 publications
(41 reference statements)
3
21
0
Order By: Relevance
“…NBF was used to represent blood flow to the palm because both sites contain glabrous skin, which lacks active vasodilator capacity (Yamazaki and Sone 2006). Palm blood flow was not measured directly because this would have impeded palm contact with the cooling plate.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…NBF was used to represent blood flow to the palm because both sites contain glabrous skin, which lacks active vasodilator capacity (Yamazaki and Sone 2006). Palm blood flow was not measured directly because this would have impeded palm contact with the cooling plate.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Vascular reactivity was assessed at two representative sites with different control mechanisms: glabrous and nonglabrous area, respectively. Namely, it has been shown that the hemodynamic changes associated with acute exercise differ between these two sites (Yamazaki & Sone, 2006). The amplitude of changes, expressed as CVC as well as the time in which the changes occur during exercise differ between these two sites which might point to different control mechanisms.…”
Section: Exercise Augments the Endothelium Dependent Vasodilation In mentioning
confidence: 99%
“…In contrast, other studies have shown that exercise intensity does not affect the threshold (Johnson 1979;Wenger et al 1975;Yamazaki and Sone 2006, Table 2). Although the results of these studies are not consistent, it is possible that the threshold may be influenced by exercise intensity, if the intensity is higher (Table 2).…”
Section: Referencesmentioning
confidence: 84%